Types of Documentary Producers - Elsanecca Mona, Anak James Kunyu; Pei Pei, Leong; Abdullah Sofiuddin, Mahamud; Chong Lee, Yow (Mini Film Festival, 2022)
Infographics on types of documentary producers. The content is extracted from MFF Doc Workshop (1) presented by Ms. Cheyenne Tan, designed by Elsa, PeiPei and Abdullah, advised and edited by Yow.